Analisis Tingkat Keamanan Aplikasi SIMAK Menggunakan Standard ISO/IEC 27002:2013 (Studi Kasus: UPTTIK Universitas Siliwangi) - Iyos Rosidin Pajar (Fakultas Teknik, 2021)
The issue of data security seems to be one of the most intriguing topics to observe in the development of information technology in recent time/. The information technology related to the management processes, one of which is the SIMAK application at the University of Siliwangi needs a higher security concern. This study aims to determine the level of security of the SIMAK application in which the researchers can provide recommendations to SIMAK managers. This could be the basis for the future improvements. Researchers used 4 domains from ISO / IEC 27002: 2013, namely domain 5, it contains information security policies. Domain 6, it contains organizational information security. Domain 9, it contains access control. Lastly, Domain 11, it contains physical and environmental security. When they are specified from the four domains, 38 controls are obtained. Security, from the results of the questionnaire and weighting, the result of the 5 domains maturity value is= 1.49, the result of the domain 6 maturity value is= 1.52, while domain 9 maturity value is= 1.32 and domain 11 maturity value constitute to 1.97. If it is averaged, the Siliwangi University SIMAK application is at level 2 or repeatable.